Effect of clear-cutting and the amount of logging residue on chemical composition of percolation water in spruce stands on glaciofluvial sandy soils in southern Finland - Lindroos, Antti-Jussi; Tamminen, Pekka; Heikkinen, Juha; Ilvesniemi, Hannu
2016